2020
DOI: 10.1111/aas.13710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different mean arterial pressure targets on plasma volume, ANP and glycocalyx—A randomized trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, general anaesthesia with complete sedation and analgesia can inhibit systemic inflammation to a large extent (Chaiyakulsil et al., 2018; Sasaki et al., 2017; Vos et al., 2015). Intraoperative mean arterial blood pressure is kept very stable to ensure organ perfusion (Damén et al., 2021). The prognosis of patients in the three groups was similar, and all patients were discharged from the hospital smoothly.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, general anaesthesia with complete sedation and analgesia can inhibit systemic inflammation to a large extent (Chaiyakulsil et al., 2018; Sasaki et al., 2017; Vos et al., 2015). Intraoperative mean arterial blood pressure is kept very stable to ensure organ perfusion (Damén et al., 2021). The prognosis of patients in the three groups was similar, and all patients were discharged from the hospital smoothly.…”
Section: Discussionmentioning
confidence: 99%
“…The increases in BV in the two groups were greater than expected. The explanation of this phenomenon is that a decrease in blood pressure during the induction of anesthesia increased the plasma volume [ 17 , 18 ]. The calculated increase in plasma volume without fluid infusion during the induction of anesthesia was 10–15% [ 17 ], corresponding to a 310 to 460 mL increase in plasma volume.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] However, not all studies support this viewpoint. [ 19 , 20 ] Oscillatory shear stress caused by intravenous infusion may directly induce glycocalyx degradation, [ 10 ] indicating that the rate of intravenous infusion can also affect the glycocalyx integrity. However, recent studies showed no difference between intravenous infusion at a faster versus slower rate.…”
Section: Common Factors Of Fluid Resuscitation Affecting the Glycocalyxmentioning
confidence: 99%